In the diffuse large B-cell lymphoma microenvironment, autophagy genes are upregulated in pro-inflammatory macrophages and linked to BCL2 overexpression - Resanoa, Miguel; Delgado, Alba; Rodiño, Claudia; Villar, Marina; Aiastui, Ana; Braza, Mounia S. (Frontiers in Immunology, 2025)
Diffuse large B-cell lymphoma (DLBCL) is one of the most frequent B-cell non-Hodgkin lymphoma types. It is characterized by a complex immune microenvironment, rich in macrophages (innate immunity cells), and high aggressiveness. DLBCL cells might respond to the increased energy demand by enhancing key metabolic processes, such as autophagy in which damaged cell constituents and debris are sequestered/removed for recycling. Here, we investigated the autophagy gene expression profile in DLBCL and in non-tumor controls using publicly available gene expression datasets and a substantial cohort of patients’ tissue samples. For the first time, we describe in the DLBCL microenvironment, a differential autophagy gene expression profile characterized by overexpression of BCL2 (anti-apoptotic factor) in M1 pro-inflammatory macrophages compared with M2 immuno-suppressive macrophages. Moreover, the expression levels of CD86 (M1 macrophage marker) and CSF1R (M2 macrophage marker) were positively correlated with those of BECN1 (autophagy regulator) and BCL2 (only CD86) that were in turn correlated with MTOR expression in tumor B cells and in the CD86+ macrophage subtype. We confirmed these results by immunohistochemistry and immunofluorescence analyses of DLBCL and non-tumor tissue samples. Our finding of an autophagy-related pro-inflammatory signature highlights the crucial role of autophagy in the DLBCL immune microenvironment and suggests its potential as a therapeutic target.